Cooperative learning in teaching mathematics: the case of addition and subtraction of integers - Mate, Ileana (Teaching Mathematics and Computer Science, 2011)
In the course of teaching and learning mathematics, many of the problems are caused by the operations with integers. My paper is a presentation of an experiment by which I tried to make the acquisition of these operations easier through the use of cooperative methods and representations. The experiment was conducted in The Lower-Secondary School of Paptamási from Romania, in the school year 2009-2010. I present the results of the experiment.